Specific absorption rates (SARs) induced in head tissues by microwave radiation from cell phones. - Lin, James C. (IEEE Antennas & propagation magazine.)
The cellular/mobile phone industry has been reluctant to disclose SAR values to the public in the past. The decision by the Cellular Telecommunication Industry Association (CTIA) to require manufacturers to disclose SARs emerged after it became clear that SAR information was going to appear on the FCC Web site in a user-friendly form. It was also prompted by a British government panel's call, on May 11, 2000, for the SAR of each mobile phone to be printed on the box in which the phone is sold. The wireless telephone industry is concerned about how the public may use the SARs, because, according to one industry source, "SARs by themselves may be misleading and variations in SARs do not represent a variation in safety." Indeed, SAR values can vary as a function of the carrier frequency-for example, 850 or 1900 MHz, used to transmit the telephone message-or how the handset is held. The article presents some insights into SAR, what it is, how is it determined, and what it means.